Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires

Garçon manqué - Bouraoui, Nina (Librairie générale française, 2000)
Dans les années 70, la guerre d'Algérie est encore dans tous les esprits. Ce récit autobiographique décrit la difficulté de vivre en Algérie avec une mère française, et de vivre en France avec un père algérien
Section: 188 pages ; 18 cm
Keywords: 1900-1999; 1970-1979; afrique; afrique du nord; algérie; approches et analyses; arts; cours; discipline; europe; france; lit2815; premier cycle; périodes historiques; racisme; roman; régions géographiques; système colonial; systèmes d'oppressions; études littéraires